MESSAGE ORIENTED COMMUNICATION FOR IPV6 ENABLED PERVASIVE DEVICES - Szydlo, Tomasz; Suder, Pawel; Bibro, Jakub (Computer Science, 2013)
An increasing number of electronic devices in our environment is equipped with radio interfaces used for exposing and using their functionality by other devices and applications. Wireless communication in this class of devices is exposed to a number of situations that may occur including limited energy resources, equipment failures, nodes mobility and loss of communication between nodes. It causes that commonly used standards and protocols for sharing services are not practical and do not take into account the occurrence of these problems. The paper presents the concept of communication that relies on the exchange of messages between wireless pervasive devices available in the environment.